A study of the ground plane effect in passband filters using OSRR cells (2015)
This paper presents the study of the ground plane effect in passband filters using metamaterial cells in Open Split Ring Resonators (OSRR) structures on microstrip substrates. Three different configurations have been proposed, namely: by removing partially the ground plane of the OSRR cell back end, by windows design over the ground plane at the back end of each cell and by placing a full ground plane. The conducted analysis shows that the filter transmission response featuring a ground plane including windows proved to be the most flattened with the middle bandwidth of the three configurations. On the other hand, the performance of these filters is similar to a conventional filter based on three-pole microstrip technology but with a considerable reduction in size of about 60%.